Memorandum of understanding between Universiti Teknologi MARA and International College of Technology Kanazawa, Japan / Fakulti Kejuruteraan Elektrik - Universiti Teknologi MARA, Fakulti Kejuruteraan Elektrik (Universiti Teknologi MARA (UiTM), 2020)
UiTM and International College of Technology Kanazawa will endeavour to strengthen, promote and develop cooperation on the basis of equality and mutual benefit.